Retinal aging in the diurnal Chilean rodent (Octodon degus): histological, ultrastructural and neurochemical alterations of the vertical information processing pathway - Szabadfi, Krisztina; Estrada, Cristina; Fernandez-Villalba, Emiliano; Tarragon, Ernesto; Setalo Jr., Gyorgy; Izura, Virginia; Reglodi, Dora; Tamas, Andrea; Gabriel, Robert; Herrero, Maria Trinidad (Frontiers in Cellular Neuroscience, 2015)
The retina is sensitive to age-dependent degeneration. To find suitable animal models to understand and map this process has particular importance. The degu (Octodon degus) is a diurnal rodent with dichromatic color vision. Its retinal structure is similar to that in humans in many respects, therefore, it is well suited to study retinal aging. Histological, cell type-specific and ultrastructural alterations were examined in 6, 12 and 36 months old degus. The characteristic layers of the retina were present at all ages, but slightly loosened tissue structure could be observed in 36-month-old animals both at light and electron microscopic levels. Elevated glial fibrillary acidic protein expression was observed in Müller glial cells in aging retinas. The number of rod bipolar cells and the ganglion cells was reduced in the aging specimens, while that of cone bipolar cells remained unchanged. Other age-related differences were detected at ultrastructural level: alteration of the retinal pigment epithelium and degenerated photoreceptor cells were evident. Ribbon synapses were sparse and often differed in morphology from those in the young animals. These results support our hypothesis that (i) the rod pathway seems to be more sensitive than the cone pathway to age-related cell loss; (ii) structural changes in the basement membrane of pigment epithelial cells can be one of the early signs of degenerative processes; (iii) the loss of synaptic proteins especially from those of the ribbon synapses are characteristic and (iv) the degu retina may be a suitable model for studying retinal aging.